Longitudinal study in male swimmers: a hierachical modeling of energetics and biomechanical contributions for performance - Costa, Mário Jorge (2013)
The aim of this study was to assess the pooled and individual response of male swimmers over two consecutive years of training and identify the energetic and biomechanical factors that most contributed for the final performance. Nine competitive swimmers (20.0 ± 3.54 years old; 10.1 ± 3.41 years of training experience; 1.79 ± 0.07 m of height; 71.34 ± 8.78 kg of body mass; 22.35 ± 2.02 kg·m(-2) of body mass index; 1.86 ± 0.07 m of arm span; 116.22 ± 4.99 s of personal record in the 200 m long course freestyle event) performed an incremental test in six occasions to obtain the velocity at 4 mmol of blood lactate (V4) and the peak blood lactate concentrations (Lapeak) as energetics, and the stroke frequency (SF), stroke length (SL), stroke index and swim efficiency as biomechanical variables. Performance was determined based on official time's lists of 200 m freestyle event. Slight non-significant improvements in performance were determined throughout the two season period. All energetic and biomechanical factors also presented slight non-significant variations with training. Swimmers demonstrat-ed high inter-individual differences in the annual adaptations. The best performance predictors were the V4, SF and SL. Each unit of change V4, SF and SL represented an enhancement of 0.11 s, 1.21 s and 0.36 s in performance, respectively. The results show that: (i) competitive male swimmers need at least two consecutive seasons to have slight improvements in performance, energetics and biomechanical profiles; (ii) major improvements in competition performance can be accomplished by improving the V4, SF and SL based on the individual background. Key PointsElite swimmers are able to demonstrate slight changes in performance, energetic and biomechanical characteristics at least during two seasons of training;Additional improvements in competition performance can be accomplished by manipulating the V4, SF and SL based on the individual background.Each unit of change V4, SF and SL represent an enhancement of 0.11 s, 1.21 s and 0.36 s in performance, respectively.